The “datafication” of teaching: can teachers speak back to the numbers? - Stevenson, Howard (Taylor and Francis, 2017)
Teachers face considerable and increasing pressure in their working lives. Labor intensification compels teachers to work faster, harder, and longer. However, teachers also experience increasing external control over what they teach and how they teach. These processes are increasingly made possible by the “datafication” of teaching, whereby the educational process is increasingly transformed into numbers that allow measurement, comparison, and the functioning of high-stakes accountability systems linked to rewards and sanctions. Although there is no question that being able to use student assessment data to support learning has an important place in teachers' repertoire of skills, “datafication” refers to the use of data in a way that has become increasingly detached from supporting learning and is much more concerned with the management of teacher performance as an end in itself. This article presents two currents of critical thought in relation to teachers' work, labor process theory and poststructural analyses grounded in the concept of performativity, and discusses them as a way of “making sense” of teachers' work and the “datafication” of teaching, with a particular focus on questions of control and resistance.